2010
DOI: 10.1111/j.1365-2516.2009.02160.x
|View full text |Cite
|
Sign up to set email alerts
|

An improved manufacturing process for Xyntha/ReFacto AF

Abstract: ReFacto Antihemophilic Factor is a second-generation antihaemophilia A product manufactured using a process that includes therapeutic grade human serum albumin (HSA) in the cell culture medium, but is formulated without HSA as a stabilizer. Even though this second-generation antihaemophilia product has a good safety profile, a programme was implemented to eliminate all animal- and human-derived raw materials from the production process, thus producing a third-generation product. To that end, HSA has been remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 14 publications
0
39
0
Order By: Relevance
“…These cleavages also release the a3 acidic domain from the N-terminus of the LC, which is required for Von Willebrand factor (VWF) binding to FVIII, as well as the remaining 14 amino acids of the B domain [13]. It has been reported that in a number of recombinant factor FVIII molecules [14][17], the cleavage at R1648 does not occur for a fraction of the secreted BDD rFVIII product, leading to the generation of non-processed single chain rFVIII isoform. Also, there are recent reports on different isoforms of SC rFVIII designed to improve in vivo activity and prolong half-life [18][20].…”
Section: Introductionmentioning
confidence: 99%
“…These cleavages also release the a3 acidic domain from the N-terminus of the LC, which is required for Von Willebrand factor (VWF) binding to FVIII, as well as the remaining 14 amino acids of the B domain [13]. It has been reported that in a number of recombinant factor FVIII molecules [14][17], the cleavage at R1648 does not occur for a fraction of the secreted BDD rFVIII product, leading to the generation of non-processed single chain rFVIII isoform. Also, there are recent reports on different isoforms of SC rFVIII designed to improve in vivo activity and prolong half-life [18][20].…”
Section: Introductionmentioning
confidence: 99%
“…BDD-rFVIII was isolated from an rFVIII-expressing CHO cell line, which has secreted rFVIII that consistently contains HC fragments with varying portions of the B domain including one that entirely lacks the B domain. Its appearance in 1-D SDS-PAGE was similar to that of ReFacto/Xyntha [6] and N8 [19], as it contained two major bands representing the HC and LC (Fig. 1).…”
Section: Peg-rfviii 0854psr (Dop 5) Cy3 Peg-rfviii 09004psr (Dop 2) Cy5mentioning
confidence: 77%
“…Current substitution therapy uses plasma-derived and recombinant factor VIII (rFVIII) products, the latter comprising full-length and B-domain-deleted (BDD) variants [4][5][6]. BDD-rFVIII was developed because the B domain of FVIII is apparently not required for the catalytic activity of FVIIIa.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first reported use of a 15 nm nanofilter in the manufacturing process of a rFVIII product. The viral clearance resulting from the manufacturing process of rFVIIIFc can be compared with that of another rFVIII product produced in mammalian (CHO) cells [6]. The CHO-based rFVIII process achieved >11.4 logs for X-MLV, >14.0 logs for SuHV-1, >10.3 logs for Reo-3, and 5.2 logs for MMV.…”
Section: Discussionmentioning
confidence: 99%